Common Institutional Investors’ Shareholding, Enterprise Export and Financialization of Entity Enterprises: Empirical Evidence from Listed Companies in China - Cui, Mingrui (Transactions on Economics, Business and Management Research, 2024)
Based on the panel data of listed companies in China from 2008 to 2016, this paper conducts a theoretical analysis and empirical test on the relationship among common institutional investors’ shareholding, enterprise export, and the financialization of entity enterprises. This paper uses the fixed effect regression model to estimate and find the following results: First, enterprise exports will promote the financialization of entity enterprises; Second, holding shares by common institutional investors will weaken the positive role of enterprise exports in the financialization of entity enterprises. The above results are instructive for policymakers and enterprises to improve corporate governance and optimize the allocation of financial capital.